MR imaging, CT, and angiography features of endolymphatic sac tumors: report of two cases - BALTACIOĞLU, FEYYAZ (SPRINGER, 2002)
Low-grade adenocarcinoma of endolymphatic sac origin is a rare tumor of the temporal bone. There are some difficulties in its differential diagnosis from other vascular and non-vascular tumors of the temporal bone. However its radiological differentiation from other tumors of the temporal bone is important for surgical planning. We present a report on two endolymphatic sac tumors with some specific radiological findings which can support a correct diagnosis.
Keywords: adenocarcinoma; endolymphatic sac; MR imaging; CT; angiography; AGGRESSIVE PAPILLARY TUMOR; LOW-GRADE ADENOCARCINOMA; TEMPORAL BONE; ORIGIN; ADENOMA